Front Cover: Metastable Nanoporous Palladium Evolving from Palladium Nanocrystals (ChemNanoMat 10/2021). Issue 10 (12th September 2021) - Teraji, Satoshi; Samitsu, Sadaki; Tran‐Cong‐Miyata, Qui; Norisuye, Tomohisa; Nakanishi, Hideyuki
Abstract : Palladium nanocrystals can be structurally evolved into metastable nanoporous palladium with catalytic activity toward ethanol electrooxidation. The resultant palladium structure has bimodal pore distribution and a large electrochemically active surface, and its catalytic activity can be enhanced through the structural evolution of palladium nanocrystals. The proposed method is simple and based on an easy process that excludes treatments in high temperature, high vacuum, or inert gas environments, and is thus suitable for mass production of palladium electrocatalyst. More information can be found in the Communication by Nakanishi et al.